Assessing the Dimensions of Solat from the Perspectives of the Quran and Hadith - Yasin, Najibah; Salleh, Faridah; Muhamad Isa, Rabiatul Aribah; Dollah Hamdani, Siti Rafidah; Mat Dan, Aisah; Mohd Noor, Noor Fadhzana; Daoh, Muhammad (Selangor Humaniora Review, 2020)
Solat is the most important pillar in Islam. The objective of this paper is to assess the dimensions of solat from the two main sources of Islam which are the Qur’an and hadith of the Prophet (PBUH). These dimensions may assist in examining the implications of solat. This study employed content analysis, a qualitative descriptive design, to analyse the data. The findings show that the Qur’an and hadith of the Prophet reveal at least four dimensions of the solat, namely spiritual, social, physical, and cognitive dimensions. The present study recommends that the revealed dimensions of solat can be further examined and included in Islamic education syllabus for the purpose of enhancing the implication-based education in Islamic teaching.